Nanohybrid and nanocomposite materials from kaolinite - El Bokl, Tamer A (University of Ottawa (Canada), 2007)
A variety of organic moieties, including biodegradable polyesters, were intercalated into the interlayer spaces of kaolinite, a naturally occurring clay mineral, in an attempt to explore and extend its interlamellar chemistry. Several novel intercalated nanohybrids of kaolinite and cyclic imides were synthesized by simply performing the reactions at ambient temperatures. Intercalation is generally achieved by displacing the pre-intercalated guest organic molecules from the intermediate intercalate. The complete displacement of the guest molecules by the cyclic imides was confirmed by the results of XRD and 13C NMR analyses. The interaction between the intercalated molecules and the interlamellar surfaces of kaolinite was studied by FTIR analysis. Furthermore, the intercalation of alditols, adonitol and D-sorbitol, into the interlamellar spaces of kaolinite was achieved, and the grafting of the hydroxyl groups of these alditols onto the aluminol internal surfaces of kaolinite followed the intercalation via thermal treatment. Also, the modification of the interlamellar surfaces of kaolinite by the direct grafting of two different alditols, namely, D-mannitol and dulcitol, from the melt is reported. Several starting materials were used among which the kaolinite--DMSO intercalate was the most effective. This was done directly from the alditol melt at temperatures just above the melting point of these polyols. The intercalated polyols are arranged in a flattened monolayer arrangement, as indicated by the interlayer expansions. 13C CP/ and DD/MAS NMR indicated the complete replacement of the DMSO by the alditol, and that the alditols were rigidly constrained in the interlamellar spaces of kaolinite. Thermal analysis shows that the loss of the grafted alditols coincides with the dehydroxylation of the kaolinite layers. The intercalation process was followed with time in the case of adonitol. The reaction proceeds via a partial collapse of the Kao--DMSO intercalate before the steps corresponding to the intercalation of adonitol. In addition, a new family of kaolinite--polymer nanocomposites was prepared by the intercalation of a series of biodegradable polyesters in the interlayer spaces of kaolinite. The intercalation was achieved directly from the polymer melt. The results of the TGA/DTA analyses showed enhanced thermal stabilities of the produced nanohybrids and nanocomposites compared to the starting materials. Finally, promising attempts that involved alternative synthesis strategies for the preparation of kaolinite--polymer nanocomposites are presented.
Keywords: Chemistry, General.; Chemistry, Organic.